Household Preferences and Willingness to Pay for Waste Management Services in Rural Nigeria - Edeme, Richardson Kojo; Nkalu, Nelson C. (American Economic & Social Review, 2018)
Safe and clean environment is an essential requirement for maintaining life on earth and creating human friendly environment is one of the most important issues in the world today. The concern of this paper is to examine household preference and willingness to pay for waste management services. The population of the study is made up of the households in the Nsukka urban where simple random sampling techniques was employed to select 25 households from each of the six town in Nsukka urban, employing binary modelling using probit model to estimate the impact of both cultural and demographic factors and economic factors on household willingness to pay for waste management service. The result revealed that demographic factors such as age, household size and education have great influence on household willingness to demand for waste management in Nsukka urban area. Also, economic factors such, income level of the households, awareness of the household about the environment, impact of waste management service and cost of waste management service has positive significant impact on household willingness to pay for waste management services.